Consistency of Two Plastic Strengthening Parameters from EH36 Steel. (1st March 2023) - Liu, Xianru; Li, Jianguang; Ren, Yi; Zhao, Kuangjie
Abstract: In order to study the consistency of the two plastic hardening parameters applied to the constitutive model, EH36 marine steel was selected as the experimental material in this paper, and the stress-strain relationship curve of EH36 steel was obtained through uniaxial tensile experiments at room temperature, and elastic-power hardening was used. The model fits the stress-strain curve of EH36 steel and obtains the fitted parameters. Then we select a certain plastic strain arbitrarily, take the effective plastic strain and plastic work as the hardening parameters, respectively, and use the kinematic hardening model to calculate the one-dimensional stress-strain relationship of the reverse loading of the two hardening parameters when the pre-strain is applied. The consistency of the two plastic hardening parameters is demonstrated according to the calculated relationship.